LABORATORY WORK ON TOTAL SUCTION CALIBRATION CURVE FOR WHATMAN #42 FILTER PAPER - Yusep Muslih Purwana (Jurnal Riset Rekayasa Sipil, 2017)
Soil suction is one of main parameter in unsaturated soil mechanics as its measurement is as very important as pore water pressure measurement for effective stress concept in saturated soil mechanics.Basically, the measurement of soil suction can be classified into 2 categories; direct and indirect method. In the first method, negative pore water pressure is measured directly to obtain matric suction, whereas in indirect method, suction is obtained indirectly by using salt solution and censor.  Calibration is then required to establish the relationship between concentration of salt solution and censor. Filter paper method is considered as the simplest method and relatively low cost compare to other method. The studies conducted by many investigators indicate that calibration curve from one type to another type of filter paper is quite different. This paper presents the basic concepts of laboratory work on establishing total suction calibration curve for Wahtmann #42 filter paper. The work has been conducted using NaCl and KCl solutions with different molality to generate different suction. The result indicates that the higher molality of solution, the higher suction is generated. The calibration curve from KCl exhibits a bit higher compare to the one from NaCl. The difference of both curves most probably is due to the difference of equilibration period and suction source.Keywords: Calibration curve, filter paper, suction, unsaturated soil